1955
DOI: 10.1111/j.1365-2621.1955.tb16858.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Degree of Enzyme Inactivation and Storage Temperature on Quality Retention in Frozen Peas

Abstract: The necessity of blanching (scalding) vegetables to be preserved by freezing has been recognized since the report by Joslyn and Cruess (12) in 1929. The deterioration in flavor and color and the off-odors which develop in raw or under-blanched vegetables during freezing storage have been ascribed to the action of enzymes. I n many instances, the enzyme sytem or systems responsible for the deteriorative changes have not been identified. Nevertheless, it has become common practice t o use certain enzyme tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1956
1956
1988
1988

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Activity in Lot 5 decreased with storage. Dietrich et al (1955) and Pinsent (1962) also noted an increase in POD activity during storage at -18°C in green peas blanched for 60 set at 93-100°C. Pinsent noted that activity increased only over the first 4 months in storage.…”
Section: Resultsmentioning
confidence: 83%
“…Activity in Lot 5 decreased with storage. Dietrich et al (1955) and Pinsent (1962) also noted an increase in POD activity during storage at -18°C in green peas blanched for 60 set at 93-100°C. Pinsent noted that activity increased only over the first 4 months in storage.…”
Section: Resultsmentioning
confidence: 83%
“…Ascorbic acid and sulfhydryl compounds are also found in asparagus and are oxidizable. While ascorbic acid retention in frozen vegetables as a function of blanching time has been previously investigated (Hartzler and Guerrant, 1952;Dietrich et al, 1955) sulfhydry1 content in asparagus is of particular interest because asparagus contains several sulfhydryl compounds related to flavor (Tress1 et al 1977b). The present study was undertaken to determine the relationship between blanching time and hexanal in a single lot of asparagus during frozen storage.…”
Section: Introductionmentioning
confidence: 99%
“…No reactivation has been shown in frozen peas blanched 90 set or more, the time required to pass the commercial test. Other investigators also observed peroxidase regeneration in peas that had been blanched just enough to reduce the original peroxidase activity (Dietrich et al, 1955 ;Pinsent, 1962).…”
Section: Resultsmentioning
confidence: 92%